Adaptive clothing is really adaptive? A lens view of ‘awareness towards adaptive clothing in Hyderabad - Kusuma, P.Gowri; Vejju, Balaji; Sarma, KSR; Johri, Shubhra; Vijaya, E.; Reddy, A Subhash (Edelweiss Applied Science and Technology, 2024)
‘Real style is never right or wrong, it is a matter of being yourself on purpose’ – G.Bruce Boyer. This statement by Bruce Boyer is not only apt to the younger generation, or the so-called fashion freaks or style lovers, but applicable to everyone who wish to dress themselves the best. The dilemma is, how many are able to wear (clothes) according to their needs? We have exclusive wear for new-borns, and occasions, but have we ever thought of having exclusive designs for specially abled and aged people as their needs are totally different. This paper is aimed at understanding the issues and challenges of clothing of geriatric citizens and their awareness towards the concept of adaptive clothing. The study was carried out using convenient sampling where paid old age homes in Hyderabad were considered for the study. The researchers made an attempt to contact the managers/care takers of these paid old age homes. Initially dialogues were exchanged to sensitize the managers/care takers towards adaptive clothing followed by focused group discussions with the geriatric citizens. These discussions revealed that majority of the geriatric people are not aware of adaptive clothing and they would love to try adaptive clothing and this would enhance their life style and build confidence in them. The researchers tried to identify the factors which promote the adoption of adaptive clothing among old age people. The study revealed that the major factor is lack of awareness. Other factors which contribute for the adoption of adaptive clothing are cost, ease of availability, customization, size availability and fabric type. Though this is a niche study, this study will have major implications on the society and their perceptions towards clothing needs for geriatric people. The textile industry can draw inferences from this study and try to create a new product and penetrate into new market.